Observações sobre o comportamento de flebotomíneos em ecótopos florestais e extraflorestais, em área endêmica de leishmaniose tegumentar americana, no norte do Estado do Paraná, sul do Brasil Observations on the behavior of phlebotomines in forest and domiciliary environments in an endemic area of American cutaneous leishmaniasis in southern Brazil - Ueslei Teodoro; Vicente La Salvia Filho; Edson Maurício de Lima; Roberto Palma Spinosa; Orlando Carlos Barbosa; Maria Eugênia Moreira Costa Ferreira; Maria Valdrinez Campana Lonardoni (Universidade de São Paulo, 1993)
De novembro de 1988 a abril de 1990 capturaram-se 75.637 flebotomíneos, com armadilhas luminosas de Falcão, na fazenda Palmital, Norte do Estado do Paraná, Brasil, resultando quinze espécies. Dos insetos capturados, 95,8% o foram nos ambientes domiciliar e peridomiciliar e os restantes 4,2%, no ambiente florestal. Da totalidade de flebotomíneos, 82,0% foram capturados numa armadilha instalada dentro de um abrigo de galinhas. Dos flebotomíneos capturados em todas as armadilhas, 93,8% eram representados pelas espécies Lutzomyia migonei, Lutzomyia whitmani, Lutzomyia pessoai, Lutzomyia fischeri e Lutzomyia intermedia, todas de relevância na epidemiologia da leishmaniose tegumentar americana. L. migonei prevaleceu numa única armadilha do peridomicílio e nas demais prevaleceu L. whitmani. As densidades mensais desses insetos, obtidas usando-se somente os resultados da armadilha instalada dentro do galinheiro, foram elevadas principalmente nos meses mais quentes e úmidos. No ambiente florestal predominou a acrodendrofilia dos flebotomíneos, pois 87,9% deles foram capturados nas armadilhas instaladas a aproximadamente 10 m do solo, havendo predomínio de L. whitmani, L. fischeri, L. migonei, L. intermedia, Brumptomyia brumpti, L. monticola e L. pessoai. A carência de informações sobre a epidemiologia da leishmaniose no Estado do Paraná indica que são necessários estudos que venham esclarecer quais são as implicações das relações flebotomíneos/animais domésticos na cadeia de transmissão de Leishmania no domicílio e peridomicílio. Between November 1988 and April 1990, 75,637 phlebotomines were captured with the use of Falcão light traps on Palmital farm in the north of Paraná State, Brazil. Fifteen species were represented. The percentage of 95.8% of the insects were captured within the domiciliary area and the remaining 4.2% in the forest environment. The percentage of 62 were captured in one single Falcão light trap installed in a henhouse, where Blancasmya migonei predominated. In all the other traps Psychodopygus whilmani was predominant. B. migonei, P. whitmani, Pintomyia pessoai, Pintomyia fischeri and Psychodopygus intermedius are highly significant vectors of American cutaneous leishmaniasis and represented 93.8% of all phlebotomines captured with 10 Falcão light traps. The monthly densities of these insects were obtained from one Falcão light trap installed in a henhouse and increased especially in the warmer and more humid months. In the forest environment the phlebotomines were captured principally in traps installed about 10 meters above the ground and P. whilmani, B. migonei, P. intermedius, Brumptomyia brumpti, Psychodopygus monticola and P. pessoai were the dominant species. The need for information about the epidemiology of American cutaneous leishmaniasis calls for further investigation with a view to clarifying the implications of the relationship between the phlebotomines and domestic animals in the Leishmania cycle of transmission in domiciliary areas.